Penggunaan Huruf Ba Dalam Al-Qur'an Dan Implikasinya Bagi Pembelajaran Terjemah (Analisis Fungsi dan Makna Huruf Ba dalam Surat Ali Imran) - Aziz Ferdinan Irhas; Mustajab M Making (Mustaneer : Journal of Islamic Thought and Civilization, 2025)
Effective communication relies heavily on understanding the meaning of words. Unfortunately, understanding the Qur'an is often incomplete. The data understanding of the letter "ba" which is only interpreted as "with," even though it has a various meaning. This study aims to understand the function and deepen the meaning of the letter ba, specifically in examining Surah Ali Imran. This study applies a literature study approach with the Miles and Huberman data analysis model, namely collection, reduction, presentation, and extraction. The results of the analysis showed that the letter "ba" has 13 meanings, categorized as ma'ani letters that function to make “kasrah” of the followers. However, in Surah Ali Imran, 131 letters "ba" were found in 10 different meanings: ba lil-ilshaq (true and figurative), ba lil-isti'anah, ba lis-sababiyah, ba lil-'iwadh, ba lil-badali, ba lidz-dzarfiyah, ba lil-mushahabah, ba lit-tab'idiyah, ba lil-isti'la, and ba liz-zaidah. The implication of this research is in translation learning, which provide a comprehensive understanding of the function and meaning of the letter "ba" when dealing with religious texts. This research will help in achieving accuracy and harmony in the translation process.